The effects of crude alkaloid extracted for Nerium oleander L. Leaves on biological performance of Bemisia tabaci Genn. ( Homoptera: Aleyrodida) - Munther Hamza Rathi; Fawzi Shnawa Al- Zubaidi (Al-Qadisiyah Journal of Pure Science, 2017)
In laboratory bioassays to determine the toxicity of crude alkaloid extracts of Nerium oleander leaves to whitefly Bemisia tabaci . Crude alkaloids applied at concentrations of 0.1 , 0. 2 , 0.5 , 1 , 2 % . The egg was generally the least susceptible stage to all test treatments.The results indicated that the concentration of 2 % was the most effective . At this concentration eggs mortality reached 51.35 % in crude alkaloids , differences in nymphal mortality according to age was observed at all concentrations of alkaloid extract , the first larval instar and second namphal stadium had higher mortality when treated with alkaloid extract at concentrations of 1% and 2% than third nymphal stadium . Pupal and adults mortality reached 84.66 % and 71.84% when treated with crude alkaloids at concentration of 2% respectively .Cumulative mortality reached 100 % at concentration of 1 % and 2 % in second and third nymphal stadia when treated with crude alkaloids . Development time of immature stages of B. tabaci also , affected by the application of crude alkaloids extracts of N. oleander leaves , generally development period prolonged in all treatments of alkaloids as compared with control treatment .